2010
DOI: 10.1016/j.stem.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

miR-130b Promotes CD133+ Liver Tumor-Initiating Cell Growth and Self-Renewal via Tumor Protein 53-Induced Nuclear Protein 1

Abstract: A novel paradigm in tumor biology suggests that cancer growth is driven by stem-like cells within a tumor, called tumor-initiating cells (TICs) or cancer stem cells (CSCs). Here we describe the identification and characterization of such cells from hepatocellular carcinoma (HCC) using the marker CD133. CD133 accounts for approximately 1.3%-13.6% of the cells in the bulk tumor of human primary HCC samples. When compared with their CD133⁻ counterparts, CD133(+) cells not only possess the preferential ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
304
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(322 citation statements)
references
References 45 publications
(55 reference statements)
18
304
0
Order By: Relevance
“…Comparing with Hep-11 cells, 31 mature miRNAs including those that have been reported to have a tumour-suppressor role in other types of TICs such as let-7 family members, miR-200b and miR-34a, were found to be downregulated, and 46 mature miRNAs including miR-130b, which acted as an oncomir in CD133 þ HCC TICs 21 , were upregulated significantly in Hep-12 cells (Fig. 2b).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparing with Hep-11 cells, 31 mature miRNAs including those that have been reported to have a tumour-suppressor role in other types of TICs such as let-7 family members, miR-200b and miR-34a, were found to be downregulated, and 46 mature miRNAs including miR-130b, which acted as an oncomir in CD133 þ HCC TICs 21 , were upregulated significantly in Hep-12 cells (Fig. 2b).…”
Section: Resultsmentioning
confidence: 92%
“…In fact, aberrant expression of miRNAs such as let-7, miR-34a, miR-181a, miRNA-130b in TICs has been found in a variety of tumour types. These aberrantly expressed miRNAs play essential roles in the regulation of TIC properties as either TIC suppressors or promoters [20][21][22][23][24] . Moreover, a series of critical signalling pathways involved in the regulation of TIC properties have been uncovered with the identification of the targets of these miRNAs 19,[25][26][27][28] .…”
mentioning
confidence: 99%
“…Our current observation together with what has been reported recently suggests that TP53INP1 is a direct target gene of miR-155. It has been reported that miR-130b promotes CD133 + liver tumor-initiating cell growth and self-renewal via TP53INP1 [24], so we concluded that miR-155 may regulates stem phenotype by targeting TP53INP1 in liver cancer cells. To determine the hypothesis, we firstly knock-down TP53INP1 using siRNA.…”
Section: Discussionmentioning
confidence: 61%
“…And repressing TP53INP1 significantly enhanced the ability of the CD133 À cells to initiate spheroid formation [24], but whether silencing TP53INP1 could increase the population of CD133 + cells is unknown. To investigate the effect of silencing TP53INP1 on the CD133 + cancer cell population, we firstly transfected MHCC-97H cells with siRNA of TP53INP1 or negative control (siTP53INP1 or siNC), and the suppression ratio was verified by qRT-PCR and Western blot (Fig.…”
Section: Down-regulation Of Tp53inp1 Promotes the Acquisition Of Csc-mentioning
confidence: 99%
“…This result recapitulated that in HCC cell lines in which GEP downregulated MICA and upregulated HLA-E on the cell surface, rendering them less susceptible to NK cytotoxicity. Note that in primary HCC fresh tissues, GEP þ cells contributed to less than 5% of the whole tumor bulk, which was comparable with the other hepatic CSC markers such as CD133 (25) and CD90 (26). Such a small proportion was actually in accordance with the definition of CSCs, that only a minority of cells in the tumor bulk was able to self-renew and regenerate into tumors (12).…”
Section: Gep Blockade By Anti-gep Antibody A23 Sensitizes Hcc Cells Tmentioning
confidence: 62%